Economic history of Northern Turkmenistan during the Mamunid period: crafts and trade - Allaberdieva Lale Agageldievna (Studia Humanitatis, 2025)
The Mamunids are the second dynasty that ruled Khorezm from 995 to 1017. The territory of the Mamunids state mainly covered the territory of the historical and cultural region of Khorezm, which had developed in ancient times in the lower reaches of the Amu Darya on the left and right banks of the mighty Central Asian river. The Mamunids dynasty left a bright mark in the history of civilization. The Mamunids era was a period of economic prosperity and the rise of trade relations between Central Asia and Eastern Europe. The article reflects the economic sphere of Khorezm under the rule of the state of the Khorezmshahs of the Mamunids.